Rate of kidney function decline and factors predicting progression of kidney disease in type 2 diabetes mellitus patients with reduced kidney function: A nationwide retrospective cohort study. Issue 6 (6th March 2020) - Kaewput, Wisit; Thongprayoon, Charat; Chewcharat, Api; Rangsin, Ram; Satirapoj, Bancha; Kaewput, Chalermrat; Suwannahitatorn, Picha; Bathini, Tarun; Mao, Michael A.; Cato, Liam D.; Harrison, Andrew M.; Vaitla, Pradeep; et al.
Abstract: Currently, the data on independent risk factors for the progression of kidney disease in type 2 diabetes mellitus (T2DM) patients with CKD are limited. This study aimed to investigate CKD progression in T2DM patients who have reduced kidney function with baseline estimated glomerular filtration rate (eGFRs) between 15 and 59 mL/min/1.73 m 2 . This study was composed of a nationwide retrospective cohort of adult T2DM patients from 831 public hospitals in Thailand during the year 2015. T2DM patients with CKD stages 3 and 4 were followed up, until development of CKD stage 5, requirement of chronic dialysis, loss to follow‐up, death, or 31 May 2018, whichever came first. Cox proportional hazard regression was utilized for analysis. A total of 8464 participants were included; 30.4% were male. The mean age was 69 ± 10 years. The mean eGFR was 45 ± 11 mL/min/1.73 m 2 . The incidence of CKD stage 5 or the need for chronic dialysis was 16.4 per 1000 person‐years. The annual rate of eGFR decline during a mean follow‐up of 29 months was −2.3 mL/min/1.73 m 2 ; 14.4% had a rapid decline in eGFR. The risk factors associated with progression to CKD stage 5 or the need for chronic dialysis were diabetes duration, systolic blood pressure, serum uric acid, albuminuria, and baseline eGFR. Conversely, older age and the use of renin‐angiotensin aldosterone system blockade were associated with decreased risks for rapid CKD progression and incidence CKD stage 5 or dialysis. This study identifies multiple predictive risk factors that support a multifaceted approach to prevent progression of advanced CKD.